High Relative Humidity‐Induced Growth of Perovskite Nanowires from Glass toward Single‐Mode Photonic Nanolasers at Sub‐100‐nm Scale - Zhiqiang Wang; Xinkuo Li; Chenduan Chen; Minhan Lou; Jiajia Wu; Kai Gao; Zengling Li; Ke Sun; Zhou Li; Zhu Xiao; Linhan Li; Pan Wang; et al. (Advanced Science)
Abstract Metal halide perovskites (MHPs) have achieved substantial progress in their applications; however, their ionic crystal character and low formation energy result in poor structural stability and limited morphological tunability. In particular, high relative humidity (RH) commonly causes severe MHP degradation, which poses a major obstacle to long‐term device operation. Herein, high RH‐induced growth of anisotropic MHP structures on glass surfaces is reported under 25 °C and atmospheric conditions on a basis of glass corrosion by moisture. Nanowires (NWs) with tunable length and composition are obtained under 85% RH air, and water molecule‐induced facet engineering of perovskite is established for anisotropic growth. Importantly, single‐mode photonic lasing in these MHP NWs with thickness at sub‐100‐nm scale (down to 75 nm ∼ 1/7 lasing wavelength) is achieved via both one‐photon and multiphoton pumping. These nanowire lasers exhibited high quality factor (>3000), high degree of polarization (≈0.9), and excellent stability under laser irradiation. The work not only presents a distinctive technique for the growth of MHPs but also endows MHP NWs with new opportunities for nonlinear optics, strong light‐matter interactions, and active photonic integrated devices.